Using local materials, mastering simplicity through complexity: The distinctive charm of the Illustrated Holy Book: Review of “Visual Narratives: Illustrated Editions of the Catholic Bible in the Ming and Qing Dynasties” - QIU, Hui (Journal of Research for Christianity in China (JRCC), 2022)
Visual Narratives: Illustrated Editions of the Catholic Bible in the Ming and Qing Dynasties. Edited and Collated by Ye Nong and Wu Qing Guangzhou: Jinan University Macau Research Institute; Macau: Cultural Association 2020. Trim size: 16mo. 503,000 characters. Black-and-white illustrations. Preface: 8 pages. Main text: 379 pages.